2022
DOI: 10.1128/jvi.02013-21
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Main Proteases of Coronavirus Bound to Drug Candidate PF-07321332

Abstract: The current pandemic of multiple variants has created an urgent need for effective inhibitors of SARS-CoV-2 to complement vaccine strategies. PF-07321332, developed by Pfizer, is the first orally administered coronavirus-specific main protease inhibitor approved by the FDA.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…Recently, the crystal structures of GC376 and PF-07321332 in complex with SARS-CoV-2 M pro have been solved. 19 , 27 All of them form a C-S covalent bond with the catalytic cysteine and display a lactam ring at the P1 position ( Figure 4 ), which is suitable to occupy the S1 pocket by forming several hydrogen-bonding interactions with Phe140, His163, and Glu166. The binding pattern of PF-07304814 as well as PF-00835231 is similar to that of GC376 at the P2 position.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the crystal structures of GC376 and PF-07321332 in complex with SARS-CoV-2 M pro have been solved. 19 , 27 All of them form a C-S covalent bond with the catalytic cysteine and display a lactam ring at the P1 position ( Figure 4 ), which is suitable to occupy the S1 pocket by forming several hydrogen-bonding interactions with Phe140, His163, and Glu166. The binding pattern of PF-07304814 as well as PF-00835231 is similar to that of GC376 at the P2 position.…”
Section: Resultsmentioning
confidence: 99%
“…The trifluoromethyl group, instead, is important to anchor the inhibitor at the S4 subpocket by forming a stabilizing contact with Gln 192 and two ordered small molecules positioned in this site. 87 , 90 …”
Section: Electrophilic Warheads In Covalent Sars-cov-2 M Pr...mentioning
confidence: 99%
“…The usual Îł-lactamic ring fits into the S1 pocket and interacts with His 163 and Glu 166 , while the dimethyl-bicycloproline group is collocated into the hydrophobic S2 pocket and is surrounded by the side chains of His 41 , Met 49 , Tyr 54 , Met 165 , and Gln 189 , resulting in extensive van der Waals interactions. The trifluoromethyl group, instead, is important to anchor the inhibitor at the S4 subpocket by forming a stabilizing contact with Gln 192 and two ordered small molecules positioned in this site. , …”
Section: Electrophilic Warheads In Covalent Sars-cov-2 Mpro Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have also identified inhibitors against novel coronavirus Mpro, including boceprevir, GC-376, and calpain inhibitors II and XII, which are often mimetic peptides that mimic natural peptide substrates and covalently bind to residue C145 in Mpro to exert inhibitory effects. (56). And a study selected 47 from the list of 3987 FDA-approved drugs for in vitro 3CLpro enzyme inhibitor screening test, and observed that boceprevir, ombitasvir, paritaprevir, tipranavir, and micafungin showed partial inhibition, and ivermectin blocked.…”
Section: Pathogenetic Characteristics Of Sars-cov-2 Virusmentioning
confidence: 99%